2012
DOI: 10.1134/s0006297912080044
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric approaches to study enveloped viruses: New possibilities for structural biology and prophylactic medicine

Abstract: This review considers principles of the use of mass spectrometry for the study of biological macromolecules. Some examples of protein identification, virion proteomics, testing vaccine preparations, and strain surveillance are represented. Possibilities of structural characterization of viral proteins and their posttranslational modifications are shown. The authors' studies by MALDI-MS on S-acylation of glycoproteins from various families of enveloped viruses and on oligomerization of the influenza virus hemag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The use of mass spectrometry for characterizing glycosylation in influenza viruses themselves has been comprehensively summarized in recent reviews. By using MS coupled with PNGase F treatment, Beer et al identified a list of N-linked glycosylation sites on HA1 of a circulating influenza A (H3N2), among which the NYT at position 158-160 was determined to contribute largely to the alteration of the epitopes of some neutralizing monoclonal antibodies so that these antibodies may eventually lose their capacity to neutralize the viruses. In another work by Cruz et al, the site-specific glycosylation profile of influenza A (H1N1) hemagglutinin was straightforwardly determined by HCD/CID-MS/MS with the aid of data interpretation by the Byonic search engine.…”
Section: Glycosylationmentioning
confidence: 99%
“…The use of mass spectrometry for characterizing glycosylation in influenza viruses themselves has been comprehensively summarized in recent reviews. By using MS coupled with PNGase F treatment, Beer et al identified a list of N-linked glycosylation sites on HA1 of a circulating influenza A (H3N2), among which the NYT at position 158-160 was determined to contribute largely to the alteration of the epitopes of some neutralizing monoclonal antibodies so that these antibodies may eventually lose their capacity to neutralize the viruses. In another work by Cruz et al, the site-specific glycosylation profile of influenza A (H1N1) hemagglutinin was straightforwardly determined by HCD/CID-MS/MS with the aid of data interpretation by the Byonic search engine.…”
Section: Glycosylationmentioning
confidence: 99%
“…The same codons were verified by the next-generation sequencing (NGS) analysis (see below). Furthermore, the Cys-126/Val-219 (rWSN) and Ser-126/Ile-219 (WSN strain) residues were observed in the respective M1 proteins when an approach routinely used in our laboratory (Kordyukova & Serebryakova, 2012), based on the in situ trypsin hydrolysis/matrix-assisted laser desorption/ionization time-of-flight MS (MALDI-TOF MS) analysis of electrophoretic protein bands, was applied ( Fig. 6; Supplementary Figs.…”
Section: M1 Protein Bioinformatics and Structural Analysismentioning
confidence: 99%
“…Proteomics has been largely used for the study of virus structure, test vaccine preparation, and strain identification. [112][113][114][115][116] The potential for clinical applications of MS for studying host cell interaction and analyzing biomarkers of the virus itself or linked to the host response has been reviewed elsewhere. [117] The detection of viral proteins can be performed directly in various fluids or cells from infected patients.…”
Section: Analysis Of Virusesmentioning
confidence: 99%